(untitled) (Research, Society and Development, 2020)
The World Health Organization (WHO) defines the adverse reaction to the medication as a harmful or unwanted reaction that appears after the administration of a medicines used to prevent or treat a disease or symptoms. The irrational use of medications is a serious problem and is related when the patient purchases medicines with no indication or professional guidance on their use. This leads to exposure to problems related to medications, as well as adverse reactions, directing the population to Primary Care units. In this context, there is a need for the insertion of the pharmacist providing clinical services in these units. The work aimed to carry out a systematic review of the literature of studies on Pharmaceutical Care in Basic Health Units and the impacts on the irrational use of medicines, as well as the role of the pharmacist in this process. Initially, 53 articles were selected from the SciELO, LILACS and BVS databases, where only 2 articles met the inclusion criteria of the review. It was evident that the monitoring of a professional providing Pharmaceutical Care and guiding patients to the best use of their medicines received in Primary Care is beneficial to the health of the population. Just as this professional would increase the number of assisted inhabitants, in addition to reducing the practice of self-medication. In addition, the authors of both articles also show that the importance of the pharmacist in Primary Care, acting in addition to Pharmaceutical Assistance, also in Pharmaceutical Care, presents better management of resources used in the municipality’s pharmacy.